(untitled) - Gharib Fazelniya; Akbar Kiani; Mahmood Ali Khosravi; Meisam Bandani (مسکن و محیط روستا)
The blow of winds and the movement of sands in sistan region is dependent on direction, speed and continuance of 120 days winds. Principally the first premise is that in sistan region the physical structure of human settlement (rural and urban) should harmonies with adapting condition of 120 days winds. This article focuses on investigation of adaptation of physical development of sandstorms in Tambaka village. The research method in this article is description – analytical, based on observation and field survey. Therefore, Tambaka village and its surrounding has been consider as case study in this regard. Required data and information are obtained directly from the region during the monthly and annual periods. Some of the previous data and information are analyzed based on the field experiences of the authors in the region and then are adapted to current condition. The result of studies shows that in sistan region many of the villages are located in the of sandstorms direction. One of these villages is Tambaka village. Our initial studies show that the local pattern of this village is harmonic with sand flow and also in the first six months of 2010 new texture of the village had 69 m3 sand accumulation. Thus, local pattern of the village is in harmony with the dominant climate of the region, especially movement of arranged and Aeolian sand shape. This pattern reflects the experience and knowledge of inhabitants of the village. Thus the valuable local experiences in comparison with the movement of the flow sand can suggest new fields of study to the organizer and heads of rural and urban affairs.